Primary haemophilus influenzae pyomyositis in an infant: a case report - Seçmeer, Gülten; Toyran, Müge; Kara, Ateş; Kanra, Güler; Ceyhan, Mehmet; Cengiz, Ali Bülent (The Turkish Journal of Pediatrics, 2003)
Promyositis is a term used to denote primary pyogenic infection of the skeletal muscle. Because striped muscle tissue is normally resistant to bacterial infection, pyomyositis is very rare. In tropical countries, pyomyositis accounts for about 4% of hospital surgical admission, but it is far less common in temperate climates. It is more common in adults and especially in men, but it can occur at any age. We would like to present an 8-month-old infant to make pediatricians aware of the possibility of pyomyositis in cases of a mass over muscle, or of children complaining of joint pain or muscle aches even in the infancy period.